EFFECTIVENESS OF MONOPOLY MEDIA TO IMPROVE STUDENTS’ CONCEPTUAL UNDERSTANDING OF THE EXCRETORY SYSTEM MATERIAL - Diah Aulia Eka Nurmahani; Qomariyah, Nur; Khaleyla, Firas (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking skills are one of the abilities emphasized in learning. However, critical thinking skills in biology learning at several schools in Indonesia hasn’t yet been optimal. One contributing factors is the lack of conceptual understanding as a foundation for developing critical thinking skills. This issue is particularly evident in the excretory system topic, which is considered difficult due to its numerous scientific terminologies and complex physiological processes. This study aimed to determine the effectiveness of Monopoly game as a learning medium in improving the conceptual understanding of 11th-grade high school students in excretory system material. This study uses the Research and Development (R&D) approach using the ADDIE development model. A limited trial was conducted on 14 11th-grade students at SMA Negeri 1 Waru. The effectiveness test was determined by comparing students' pre-test and post-test scores using the N-gain analysis and calculation of conceptual understanding indicators achievement. The results showed that the effectiveness test yielded an average N-gain score of 0.49, which falls into the moderate category and the indicators achievement get percentage of 79% with the category achieved, indicating that the learning media was effective in improving students' conceptual understanding of the excretory system materials. The improvement was supported by the characteristics of the Monopoly game, which is played collaboratively in groups, encouraging students to actively participate in learning through interaction, information sharing, discussion, and connecting various biological concepts to solve problems. Therefore, the excretory system Monopoly game is considered feasible as an alternative learning medium for enhancing students' conceptual understanding.